A comparison between raw and predicted mortality in a paediatric intensive care unit in South Africa - Ballot, Daynia Elizabeth; Ramdin, Tanusha (BioMed Central, 2018)
Objective: Paediatric intensive care resources are limited in sub-Saharan Africa. The mortality rate in a combined Paediatric/Neonatal Intensive Care Unit in Johannesburg, South Africa was almost double that in a dedicated paediatric intensive care unit in the same country. This study aimed to compare the raw mortality rate with that predicted with the Paediatric Index of Mortality (version 3), by doing a retrospective analysis of an existing database. Results: A total of 530 patients admitted to the intensive care unit between 1 January 2015 and 31 December 2017 were included. The raw mortality rate was 27.1% and the predicted mortality rate was 27.0% (p = 0.971). Cardiac arrest during ICU admission (p < 0.001), non-reactive pupils (0.035), inotropic support (p < 0.001) and renal disease (p = 0.002) were all associated with an increased risk of mortality. These findings indicate that the high mortality rate is due to the severity of illness in the patients that are admitted. It also indicates that the quality of care delivered is acceptable.
Keywords: Intensive care; Pediatrics; Health care rationing; Mortality audit; SDG-3: Good health and well-being